IMPLEMENTATION YAMAHA MOTORCYCLE SALES PROMOTION IN THE CV. TRI STAR KENCANA BANGKINANG KAMPAR DISTRICT - Nova Diana; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Sales promotion is a seriesof actions to get the attention of consumers and provide stimulus to prospective customers. Integrative designed to promote and offer items that are considered by customers differ in important and unique to them. This research was conducted at CV. Tri Star Kencana Bangkinang Kampar District, the objective of this study is to investigate the implementation of the campaign carried out by CV. Tri Star Kencana Bangkinang and to know the problems found by using quantitative descriptive data analysis and several theories about the implementation of sales promotion. The indicators used in this study are real, advertising, personal selling, sales promotion and publicity as a measure implementing sales promotion on the CV. Tri Star Kencana Kampar District.Data collection techniques done with interviews and questionnaires. Sampling was done by accidental sampling by chance. The data source is devided into two, namely: primary data, obtained from the documents of the company as well as the organizational structureof the company CV. Tri Star Kencana Kampar District. The results showed that the implementation of sales promotion in CV. Tri Star Kencana categorized quite good.Keyword: Marketing Mix, Advertising, Personal Selling, Sales Promotion and Publicity